Perilaku Orangtua Dalam Menstimulasi Anak Pada Masa Kandungan (Prenatal) - Purnomo, Purnomo; Sulistiono, Eko; Pramudia, Joni Rahmat; Sukmana, Cucu (Tunas Siliwangi, 2022)
Prenatal stimulation is an adult's conscious effort to develop all of each person's potential to develop optimally, in sync with the development of each child. Ideally both parent and mother can implement child stimulation within the womb. However, parents have been found to have a roadblock to application of prenatal stimulation, a lack of family social support. Benefits derived, along with parents knowing information related to stimulating children in prenatal times, parents may also become cadres that can eventually cross one another. A common goal in this study is to analyze the behavior of core family members in stimulating the development of children made by both father and mother. The study used a quantitative descriptive method using the survey method using a targeted sample of 150 domestic heads (KK). Research indicates that most parents have prenatal child stimulation behaviors, especially with 100% or total parental physical stimulation. Much of the behavior that has been done is religious and immoral by 97%, mothers' health stimulation by 80%, 61% cognitive stimulation, and a small percentage go through art of 41%. The medical condition of an expectant mother is affected by the emotional social condition of 59% of cravings and stress.